An Analysis of Household Consumption of Dairy Products - Kapaj, Ilir; Kapaj, Ana Mane (Archives of Business Research, 2021)
Household consumption of dairy products is one the major component in the total sales of the Albanian dairy industry. Therefore, understanding the factors which may significantly influence household consumption is important in the planning of farmers, processors and manufacturers. Consumers' responses to changes in price and non-price factors are basic to an economic analysis of almost all the policy decisions related to industry or government programs. Forecasting the future direction of household consumption, and how that direction might be modified through industry efforts or by national programs and policies, requires information on the relationships among prices, incomes, household characteristics and consumer demand. This study focuses on households as consuming units, explains and analyzes their purchasing behavior for dairy products. As milk is a very important component of the Albanians diet, this study explores consumer preferences for milk in Albania and also tries to determine consumers profiles based on their preferences and socio-demographic factors. To reach these objectives, this research designed a conjoint choice experiment survey and collected primary data in the most populated cities of Albania. This study provides useful information to different stakeholders including milk producers and importers. The milk industry and its marketers may benefit from this information by using it to strategically market their milk to different groups.